The Analysis Study of Comparison of Primary versus Delayed Ureteroscopy for Ureteric Stone : A Comprehensive Systematic Review - Audhi, Muhammad Riefki; Indra, Muhammad (International Medical Journal Corp. Ltd, 2024)
Background: Ureteroscopy is a preferred treatment for proximal ureteral stones, resulting in higher stone-free rates and lower re-treatment rates compared to shock wave lithotripsy. Flexible ureteroscopy is particularly beneficial for proximal ureteral stones, facilitating easier insertion and improving stone clearance. Methods: This systematic review focused on full-text articles published in English between 2014 and 2024, following the PRISMA 2020 guidelines to ensure methodological rigor. Result: The initial search yielded over 900 publications from these databases. After a detailed screening process, eight studies were selected for further in-depth review. This thorough examination of the chosen studies ensured a comprehensive and rigorous assessment of the existing literature. Conclusion: The study found no significant differences in complication rates between delayed ureteroscopy (D-URS) and primary ureteroscopy (P-URS) in terms of intraoperative or postoperative outcomes. Both groups showed similar operational times, postoperative stenting, stone-free rates, and complication rates, supporting guidelines from NICE for surgical treatment within 48 hours.